A network meta-analysis of the association between patient traits and response to regular dosing with ICS/long-acting β2-agonist plus short-acting β2 agonist reliever or maintenance and reliever therapy for asthma - Yorgancıoğlu, Arzu; Cruz, Alvaro A.; Garcia, Gabriel; Lavoie, Kim L.; Roche, Nicolas; P.G., Abhijith; Verma, Manish; Majumdar, Anurita; Chatterjee, Swarnendu (Respiratory medicine, 2023)
Current treatment for moderate–severe asthma with inhaled corticosteroid (ICS)-based therapy can follow two strategies: a single inhaler maintenance and reliever therapy (MART) regimen, or regular dosing with ICS/long-acting β2-agonist used as maintenance therapy plus a separate short acting β2-agonist reliever inhaler. It would be clinically useful to understand the potential of patient traits to influence regular dosing or MART treatment outcomes. A systematic literature review (SLR) and meta-analysis was conducted to identify specific patient traits that may predict improved clinical outcomes with regular dosing or MART. The SLR identified 28 studies in patients with moderate–severe asthma assessing regular dosing or MART treatments and reporting the traits and outcomes of interest. Network meta-regressions found no significant difference in the relative efficacy of regular dosing as compared with MART on any of the clinical outcomes (exacerbation rate, time to first exacerbation, FEV1, reliever use and adherence) for any of the patient traits (baseline lung function, baseline ACQ, age, BMI, and smoking history) evaluated. However, some trends towards traits influencing treatment efficacy were identified. Inconsistent reporting of traits and outcomes was observed between trials. The analysed patient traits evaluated in this study were associated with similar efficacy for the analysed outcomes to either regular dosing or MART; however, trends from the data observed encourage future analyses for possible identification of additional traits, or a combination of traits, that may be of interest. More comparable reporting of clinically important traits and outcomes would improve future analyses. •First NMA to assess asthma patient trait effects on relative treatment efficacy.•Trait effects on outcomes of regular dosing vs MART were evaluated.•There was no significant difference in regular dosing vs MART for any trait.•Trends warranting further investigation were identified.•Further analyses may provide new insights into trends observed in the data.